Associations of dietary sources of antioxidant intake and NAFLD: NHANES 2017–2020 and Mendelian randomization - Yue, Zilong; Jiang, Ziming; Qian, Long; Li, Lele; Qi, Xianliang; Hu, Kaifeng (Frontiers in Nutrition, 2024)
Purpose: To determine the association between dietary antioxidant sources and non-alcoholic fatty liver disease (NAFLD).Methods:In this observational study, we utilized NHANES 2017-2020 data to identify the factors associated with NAFLD in dietary antioxidant sources via weighted multivariate logistic regression models. Then, Mendelian randomization (MR) was applied to investigate the effect of dietary antioxidant sources on NAFLD at the genetic level.Results: Of the six dietary sources of antioxidants, only Vitamin E (Vit E) was significantly associated with NAFLD (OR=0.98; 95% CI: 0.97 -0.99; p = 0.001) . Upon adjusting for all covariates, it was determined that the highest quartile of dietary Vit E intake was associated with a decreased NAFLD occurrence compared with the lowest quartile of dietary Vit E intake (P<0.001).The results of IVW-MR analysis revealed an association between Vit E and NAFLD (OR = 0.028; p = 0.039).Conclusions: Our research indicates a negative and linear relationship between daily vitamin E intake and NAFLD.